2018
DOI: 10.22246/jikm.2018.39.2.154
|View full text |Cite
|
Sign up to set email alerts
|

A Case Report of a Chronic Migraine Patient Who Did Not Respond to Triptan

Abstract: Introduction: This case report assessed the effects of Korean medicine treatments on a chronic migraine patient who did not respond to triptan. Case Presentation: The patient received Korean medicine treatments, such as acupuncture, moxibustion, cupping, and herbal medication, during a hospitalization period. The effects of treatments were assessed with the Numerical Rating Scale (NRS) and migraine attack frequency. The intensity and attack frequency of migraines were significantly reduced after the complete t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…The study found that electro-acupuncture had a significant effect on chronic tension headaches. Kim et al [19] performed electro-acupuncture on Shuaigu (GB8) and Taiyang (EX-HN5), and reported that a patient, with chronic migraine that was not controlled using Western treatment methods, saw improvements in a relatively short period of time following electroacupuncture.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study found that electro-acupuncture had a significant effect on chronic tension headaches. Kim et al [19] performed electro-acupuncture on Shuaigu (GB8) and Taiyang (EX-HN5), and reported that a patient, with chronic migraine that was not controlled using Western treatment methods, saw improvements in a relatively short period of time following electroacupuncture.…”
Section: Discussionmentioning
confidence: 99%
“…Except for 2002, 2014, 2015, and 2016, studies had been conducted consistently. Out of the 41 studies, there were 18 case reports [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23], 9 case series [24][25][26][27][28][29][30][31][32], 9 randomized controlled trials [33][34][35][36][37][38][39][40][41], and 2 non-randomized controlled trials [42,43] (Tables 1-5).…”
Section: Classification By Yearmentioning
confidence: 99%